An Empirical Study on Political Communication in the Digital Age - Santekellur, Vadiraj Jagannatharao; Hosamani, A. P.; Singh, Anand (Indian Journal of Marketing, 2014)
Political communication campaign involves the usage of various forms of communication tools. It involves advertising through various commercial media, public relations using various media platforms, addressing potential voters' gatherings, propagating anti-incumbency stories, and using every social event to build a positive perception about a political party. However, in India, the elections are won based on many parameters along with political communication like, religion, region, development, caste, and money power. These are only one set of parameters, but if you look at the elections to be held in 2014, there are some very interesting challenges that have been added to these parameters. Young Indians in the age group of 18-35 years constitute 65% of the voting population, and the media consumption pattern of this young India is different. For them, the Internet is the primary medium for accessing information. Through this empirical research, an effort has been made to understand the Internet savvy audiences' perceptions about the Internet as a medium to learn about politics, and to ascertain whether political information consumed on social networking sites has any influence on the respondents' decision to vote. The study found that engagement through the Internet would be one of the very useful media for political communication, especially when one is targeting the Internet savvy voters.